Combined Fat- and Water-Suppressed MR Imaging of Orbital Tumors - Jackson, Alan; Sheppard, Scott; Johnson, Andrew C.; Annesley, Deborah; Laitt, Roger D.; Kassner, Andrea (American Journal of Neuroradiology, 1999)
BACKGROUND AND PURPOSE: The use of a high-resolution T2-weighted MR sequence, which suppresses signal from both fat and water, has been shown to be highly effective for depicting areas of inflammatory damage within the optic nerve. The ability of this sequence to show neoplastic and inflammatory orbital lesions, which may mimic neuritis, is unknown. This study was designed to examine the characteristics of such a sequence for the investigation of orbital mass lesions.METHODS: Twenty-eight patients with known or suspected mass lesions of the orbit and six healthy volunteers were recruited for study. Imaging was performed with a 1.5-T MR unit. Participants were examined by selective partial inversion recovery (SPIR) sequences with T2-weighted fast spin-echo acquisition, selective partial inversion recovery/fluid attenuated inversion recovery (SPIR/FLAIR) sequences with fast spin-echo acquisition, short tau inversion recovery (STIR) sequences with fast spin-echo acquisition, and SPIR sequences with contrast-enhanced T1-weighted fast spin-echo acquisition. Two neuroradiologists, using a randomised, blinded method, scored images for lesion presence and extent. Lesion extent was defined as the number of images with visible abnormality, and was compared with the standard of reference established at a later date by consensus review of all imaging sequences. The ability of the sequences to show the presence and extent of pathologic lesions was compared.RESULTS: The SPIR/FLAIR sequence showed both the presence and extent of orbital masses significantly better than did either STIR or T2-weighted SPIR sequences (P<.01 and P<.001, respectively). Contrast-enhanced T1-weighted SPIR images ranked better than SPIR/FLAIR images, although the difference failed to reach statistical significance. In the orbital apex, the SPIR/FLAIR technique was superior to all other techniques used. This reflected its ability to distinguish enhancing, pathologic lesions from enhancing, normal anatomy.CONCLUSION: SPIR/FLAIR is an appropriate screening technique for orbital masses and offers significant advantages over currently used fat-suppressed sequences for the investigation of orbital disease.